A review of The Communications And Multimedia Act 1998 in achieving media pluralism / Mazlina Mohamad Mangsor @ Mansoor and Prof Madya Dr Zaiton Hamin - Mohamad Mangsor @ Mansoor, Mazlina (Research Management Institute (RMI), 2011)
Achieving media pluralism is at the heart of the public interest policy in a democratic society (Just, 2009). It establishes the tenets of having different independent media owners with the availability of a variety range of contents regardless of patterns of demand (Doyle, 2002). The communications and multimedia law is expected to advance these public policy objectives via the structural regulation (ownership control), behavioral regulation (content control) and/or technical regulation (transmission control).